Study on Personality and Creativity of Orphanage Children: Exploring the link between delinquent behavior and mental health in orphanage children (Journal of Advances and Scholarly Researches in Allied Education, 2021)
Children and adolescents have always been an important focus of study for mental health researchers. Studies have highlighted emotional problems such as depression, anxiety, and difficulties in social interaction as well as behavioural problems such as hyperactivity and conduct problems in them.In spite of the psycho social factors continuing as before, a few children display inclination for delinquent behaviour. This infers that there are sure individual variables inside a kid, which makes him defenceless against submit a reprobate act. The current investigation is an endeavour to discover the connection between delinquent behaviour and psychiatric morbidity, intelligence and enthusiastic intelligence among children remaining in adolescent homes, orphanages and those living with parents.